Study protocol of group antenatal care implementation at a public women’s hospital in Brazil - Larissa Rodrigues; Fernanda Garanhani Surita; Maria Laura Costa; Odette del Risco Sánchez; Ysabelle Cristina Cardoso Marinato; Nicole Julie Scarpino (PLoS ONE, 2025)
The antenatal care is an important service offered to women during pregnancy that aims to guarantee the mother and fetus’s health. In Brazil, although the coverage of this service is high, the outcomes need to be improved. This study aims to implement a pilot study of a group antenatal care among pregnant women in follow up at a Woman´s Hospital of Universidade Estadual de Campinas, a public teaching hospital referral in women’s health. This randomized clinical trial will be conducted. The study group will be composed of a maximum of 15 women that will be followed in a group antenatal care with 11 meetings every 4 weeks or earlier, during all pregnancy period, while control group will receive the individual antenatal care. Sociodemographic data, quality of life, anxiety and depression will be assessed in women from both groups and women’s satisfaction and experience among the intervention group will be evaluated. A 5% significance level was adopted for quantitative analysis and the sample size was calculated based on ambulatory’s flow. A positive result among the intervention group is expected, mainly in providing a better antenatal experience for women and their knowledge of maternal and child health. This study was approved by the Ethics and Research Commission of UNICAMP number of approval: 25333119.2.0000.5404 and the Brazilian Registry of Clinical Trials (REBEC): RBR-8xcjmf UTN code: U1111-1243–6241. Date: jan.2025, version 1.